Selection of the best e-wallet in the Klang Valley, Malaysia: an application of the analytic hierarchy process - Islam, Rafikul; Sivanantham, Rajan Amaloo (UUM Othman Yeop Abdullah Graduate School of Business, 2022)
Parties conducting electronic businesses usually do not meet face-to-face, nor do they exchange currency or hard copies of documents hand-to-hand. When companies enter into electronic commerce transactions, choosing an electronic payment (or E-Wallet) system that will work well is a major issue. In this paper, after examining different E-Wallet systems in the Klang Valley, Malaysia, assessment criteria are identified based on previous researches and interviewing experts. Then, applying the Analytic Hierarchy Process (AHP) methodology, five top E-Wallets used in the Klang Valley are ranked. Results show that Samsung Pay is the most preferred E-Wallet system, followed by Lazada Wallet and Boost. The findings of this research are intended to be useful for both academic researchers and companies planning to adopt or to improve their electronic payment system.